Recommendations for a step‐wise comparative approach to the evaluation of new screening tests for colorectal cancer. Issue 6 (1st February 2016) - Young, Graeme P.; Senore, Carlo; Mandel, Jack S.; Allison, James E.; Atkin, Wendy S.; Benamouzig, Robert; Bossuyt, Patrick M. M.; Silva, Mahinda De; Guittet, Lydia; Halloran, Stephen P.; Haug, Ulrike; Hoff, Geir; et al.
Abstract : BACKGROUND: New screening tests for colorectal cancer continue to emerge, but the evidence needed to justify their adoption in screening programs remains uncertain. METHODS: A review of the literature and a consensus approach by experts was undertaken to provide practical guidance on how to compare new screening tests with proven screening tests. RESULTS: Findings and recommendations from the review included the following: Adoption of a new screening test requires evidence of effectiveness relative to a proven comparator test. Clinical accuracy supported by programmatic population evaluation in the screening context on an intention‐to‐screen basis, including acceptability, is essential. Cancer‐specific mortality is not essential as an endpoint provided that the mortality benefit of the comparator has been demonstrated and that the biologic basis of detection is similar. Effectiveness of the guaiac‐based fecal occult blood test provides the minimum standard to be achieved by a new test. A 4‐phase evaluation is recommended. An initial retrospective evaluation in cancer cases and controls (Phase 1) is followed by a prospective evaluation of performance across the continuum of neoplastic lesions (Phase 2). Phase 3 follows the demonstration of adequate accuracy in these 2 prescreening phases and addresses programmatic outcomes at 1 screening round on an intention‐to‐screen basis. Phase 4 involves more comprehensive evaluation of ongoing screening over multiple rounds. Key information is provided from the following parameters: the test positivity rate in a screening population, the true‐positive and false‐positive rates, and the number needed to colonoscope to detect a target lesion. CONCLUSIONS: New screening tests can be evaluated efficiently by this stepwise comparative approach. Cancer 2016;122:826–39 . © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : To provide practical guidance on how to compare new screening tests with proven screening tests for colorectal cancer, a panel of experts reviewed the literature and proposes a 4‐phase evaluation process that includes comparison with existing, proven tests but does not necessarily require randomized controlled trials with mortality as the endpoint. New screening tests can be evaluated efficiently using this stepwise comparative approach.